Relationships between Value Co-creation and Dominant Logic Service in a HealthCare Ecosystem: Bibliometric Analysis - Almeida Júnior , Braulio Rodrigues de (2023)
This article aimed to analyze how scientific production relates to the concepts of Dominant Logic Service and Value Co-creation as structuring components of a Health Care Ecosystem, indicating advances in academic research in the last 20 years. Bibliometric analysis was used as a methodology, using the Software “VosViewer”, of research data carried out on the Web of Science from 2000 to 2020. From the selection of 905, articles, titles, abstracts, and keywords were analyzed, establishing relationships between concepts and identifying reference authors, co-authorship networks, and countries where the articles were published. As a result, a recent increase in publications on the topic was detected, with a predominance of articles studying relationships between two concepts at a time. The papers that relate all the concepts are few but consistent with the trend of increasing research, demonstrating the relevance of the topic. Authors tend to be grouped by languages of origin and countries close to the countries where they carry out their academic activities. It was concluded that there is a consistent relationship between the concepts, detectable by the co-citation network, which confirms the importance of research relating the concepts of Value Co-creation and Dominant Logic Service when analyzing HealthCare Ecosystems. There is the use of a single database as a limitation of the survey. Future research can compare results from other databases and explore co-creation practices in the healthcare context in case studies and longitudinal research.